2019
DOI: 10.3390/ma12061001
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation on Microstructure, Texture and Mechanical Properties of AZ80 Mg Alloy Processed by Annular Channel Angular Extrusion

Abstract: Annular channel angular extrusion has been recently developed as a new single-pass severe plastic deformation method suitable for producing large size cup-shaped parts from cylindrical billets. In this study, the novel technology was successfully applied to commercial AZ80 Mg alloy at 300 °C, and microstructure, texture evolution, and mechanical properties were investigated. Due to severe shear deformation, the initial microstructure, including the coarse grains and large eutectic β-phases, was greatly refined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 43 publications
2
6
0
Order By: Relevance
“…This is perfectly understandable because a relatively higher temperature (350 • C) promoted more pronounced atomic diffusion and dislocation migration toward the grain boundary regions. Overall, the current results yield a relatively complete and uniform DRX structure compared with our previous results [13] in processing the same material at 300 • C, despite the larger grain size obtained, and it is believed that this is very beneficial for subsequent heat treatment. In Figure 6, the EBSD calculated grain orientation distribution (GOS) that distinguishes the DRXed grains (GOS < 2 • ) and unDRXed grains (GOS > 2 • ), as well as their relationship with the texture obtained from (0001)\discrete (0001) pole figures, are presented.…”
Section: Methodssupporting
confidence: 67%
See 3 more Smart Citations
“…This is perfectly understandable because a relatively higher temperature (350 • C) promoted more pronounced atomic diffusion and dislocation migration toward the grain boundary regions. Overall, the current results yield a relatively complete and uniform DRX structure compared with our previous results [13] in processing the same material at 300 • C, despite the larger grain size obtained, and it is believed that this is very beneficial for subsequent heat treatment. In Figure 6, the EBSD calculated grain orientation distribution (GOS) that distinguishes the DRXed grains (GOS < 2 • ) and unDRXed grains (GOS > 2 • ), as well as their relationship with the texture obtained from (0001)\discrete (0001) pole figures, are presented.…”
Section: Methodssupporting
confidence: 67%
“…Besides, despite that significant weakening of the deformation texture was achieved in the wall region, it is worth noting that there are still two dominant texture components that have appeared, as marked in the figure. In our previous study [13], it was revealed that texture component 1 was actually a typical shear texture, which has also been widely reported in ECAP with various Mg alloys. However, the striking feature is that another distinct texture component already appeared with its basal poles inclined to~0 • -15 • towards LD, which indicates that the higher temperature promoted the diversification of texture.…”
Section: Effect Of Extrusion On Microstructure and Texturesupporting
confidence: 69%
See 2 more Smart Citations
“…Therefore, large strain in the material exhibited more dislocation density lead to the formation of fine grains during this process. Therefore, undoubtedly it is evident that ECAP die angles significantly affect the deformation homogeneity and this influences the variation in microstructure [21][22][23].…”
Section: Variation Of Grain Size With Two Different Die After 2 and 4mentioning
confidence: 99%